2021
DOI: 10.1111/1753-6405.13154
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 test sites in Victoria approaching Stage 4 restrictions: evaluating the relationship between remoteness, travel time and population serviced

Abstract: Objective: In Australia, people residing remotely typically experience increased travel time to health services, and remote health services often have unfavourable population-to-provider ratios. The state of Victoria was treated as a case study and a spatial analysis investigated the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) point-of-care-test (POCT) site location (Major City, Inner Regional or Outer Regional) on the mean travel time for closest residents and the number of closest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…A recent study found intention to be vaccinated by rural people was influenced by limited vaccine appointment availability, or their local clinic not having vaccines available ( 18 ). Travel times for rural and remote people to their nearest inner-regional respiratory clinic hub (vaccination and testing) has been identified as a barrier to vaccination ( 18 , 19 ). To combat these barriers, the RFDS engaged early and often with communities and provided locally available vaccine clinics with clear messaging about availability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found intention to be vaccinated by rural people was influenced by limited vaccine appointment availability, or their local clinic not having vaccines available ( 18 ). Travel times for rural and remote people to their nearest inner-regional respiratory clinic hub (vaccination and testing) has been identified as a barrier to vaccination ( 18 , 19 ). To combat these barriers, the RFDS engaged early and often with communities and provided locally available vaccine clinics with clear messaging about availability.…”
Section: Discussionmentioning
confidence: 99%